Government-backed loan guarantee schemes for small and medium-sized enterprises: An evaluation of the credit guarantee corporation in Malaysia - Boocock, Grahame (Loughborough University Banking Centre, Loughborough University, 1995)
Governmen t-backed loan schemes have been introduced in many countries to enable small and medium-sized enterprises (SMEs) to have access to funding at a reasonable cost. This paper evaluates the schemes offered in Malaysia by the Credit Guarantee Corporation (CGC). The introduction emphasises the importance placed on the SME sector in achieving fully-industrial ised status for Malaysia, and highlights the fact that the CGC has been charged with a critical role in assisting SMEs. The paper then describes the operation of the CGC and its place within the spectrum offinance aimed at SMEs, before presenting thefindings of an empirical review. Three kzy areas are explored: the relationship between smallfirms, banks and the CGC; the level offinance additionality in evidence; and the level of economic additionality generated. In each of these areas, the CGC's effectiveness in meeting the needs of SMEs, banks and the wider economy appears to have been limited.The paper then describes a radical new Scheme introduced by the CGC and assesses whether this Schenre will enable the CGC to achieve its objectives, notably a greater degree offinance and economic additionality. Finally, the implications of the CGC's experience for other developing countries are briefly summarised.